Gated communities in China: social sustainable residential unit - Escobar Burgos, Celina (2021)
Since the 1978 economic reform, China has become one of the world’s largest economies and has undergone an astonishing process of urbanization. This urban growth is a central element of China’s national development strategy and is an on-going process. A significant part of this growth has been due to the massive rural-urban migration movement since the reduction of hukou (household registration system) control in the mid ‘80s and the relocation of citizens as a consequence of an intense process of demolition and reconstruction of existing residential communities. Hence, cities are growing at high speed to accommodate the enormous flow of people who are particularly moving towards the East Coast. This has resulted is the rapid emergence of large cities and megacities with a radical change in urban size and building typologies, where Chinese originating from completely different contexts live together in close proximity.